Genetic comparison of the red shrimp Pleoticus muelleri (Decapoda: Solenoceridae) using the barcode gene reveals the absence of cryptic speciation along its distribution - Carvalho-Batista, Abner [UNESP]; Negri, Mariana; Tamburus, Ana Francisca; Costa, Rogério C. [UNESP]; Castilho, Antonio L. [UNESP]; Zara, Fernando José [UNESP]; Mantelatto, Fernando L. (Elsevier, 2018)
Differences in biological traits (abundance, longevity, size at the onset of sexual maturity, and maximum size) appearing in populations of Pleoticus muelleri from the Western Atlantic are currently considered as phenotypic plasticity. However, they may also be related to intraspecific genetic differentiation and to the occurrence of cryptic speciation. Thus, to assess the genetic diversity and population structure of P. muelleri along its distribution range, we compared cytochrome c oxidase subunit I (COI; the barcode gene) and 16S sequences of individuals from seven localities from the southeastern coast of Brazil and Argentina. Ten polymorphic sites were observed in eleven COI haplotypes, but only one polymorphic site was observed in two 16S haplotypes. The haplotype network, maximum likelihood phylogram, and analyses of molecular variance (AMOVA) indicated the absence of genetic structure between populations, which in turn, points to the absence of cryptic speciation. Therefore, the known phenotypic variations may be indeed a consequence of different environmental conditions.
Keywords: COI; Dendrobranchiata; Genetic variability; Haplotype; Penaeoidea